2021
DOI: 10.1073/pnas.2025445118
|View full text |Cite|
|
Sign up to set email alerts
|

Chemotactic movement of a polarity site enables yeast cells to find their mates

Abstract: How small eukaryotic cells can interpret dynamic, noisy, and spatially complex chemical gradients to orient growth or movement is poorly understood. We address this question using Saccharomyces cerevisiae, where cells orient polarity up pheromone gradients during mating. Initial orientation is often incorrect, but polarity sites then move around the cortex in a search for partners. We find that this movement is biased by local pheromone gradients across the polarity site: that is, movement of the polarity site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 62 publications
1
23
1
Order By: Relevance
“…Wandering of the polar cap is important for sensitive gradient tracking (Dyer et al, 2013), and so the small difference in the ability to track the gradient very well that we see in the p*RGS mutant (Fig 1) may be because of its decreased offset between the receptor-driven large G-protein and the Cdc42 driven polarity machinery. In addition, an offset between receptor signaling and the polar cap has recently been proposed to play a role in gradient tracking (Ghose et al, 2021), and although we did not see an effect on gradient tracking here, under more difficult tracking conditions, the observed Gα offset may enhance chemotropic growth.…”
Section: The Role Of Rgs Phosphorylation In the Pheromone Responsecontrasting
confidence: 56%
“…Wandering of the polar cap is important for sensitive gradient tracking (Dyer et al, 2013), and so the small difference in the ability to track the gradient very well that we see in the p*RGS mutant (Fig 1) may be because of its decreased offset between the receptor-driven large G-protein and the Cdc42 driven polarity machinery. In addition, an offset between receptor signaling and the polar cap has recently been proposed to play a role in gradient tracking (Ghose et al, 2021), and although we did not see an effect on gradient tracking here, under more difficult tracking conditions, the observed Gα offset may enhance chemotropic growth.…”
Section: The Role Of Rgs Phosphorylation In the Pheromone Responsecontrasting
confidence: 56%
“…Induction of Ste5-CTM expression caused cells to arrest in G1 and make a strong but mobile polarity site (Fig. 5B) (McClure et al, 2015;Ghose et al, 2021). We quantified how long it took polarity sites of partner cells to encounter each other in mating mixes, and asked if encounters resulted in commitment (cessation of movement).…”
Section: Mating Without Mapk-mediated Adaptive Pathwaysmentioning
confidence: 99%
“…1Cii). This hypothesis is based on the observation that the direction of polarity site movement is biased by the Far1 pathway responding to local pheromone gradients (Ghose et al, 2021). Simulations have shown that the pheromone gradient is very steep when the polarity sites in partner cells are near each other (Clark-Cotton et al, 2021), but upon reaching alignment there would be no net gradient across the well-centered polarity site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have focused on the gradient generated by the regulation of ATPase, the regulation of the concentration gradient via phosphorylation-dephosphorylation reactions is ubiquitous. Therefore, the chemophoresis engine resulting from the regulation of the hydrolysis of other factors, such as GTPase, should work for a variety of intracellular processes [77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%